Optimal cut‐off for hourly lactate reduction in ICU‐treated patients with septic shock. Issue 7 (2nd April 2019) - Promsin, Panuwat; Grip, Jonathan; Norberg, Åke; Wernerman, Jan; Rooyackers, Olav
Abstract : Background: A decrease in lactate concentration over time during septic shock is associated with favourable outcomes. However, if this applies to hourly intervals during the initial time period in the ICU is unknown. The aim of this study was to investigate whether there is an early hourly reduction rate of lactate that is related to clinical outcome in septic shock patients treated in the ICU. Methods: A cohort of adult septic shock patients admitted to the ICU with an initial lactate level >2 mmol/L and receiving vasopressor was retrospectively analysed. Mean hourly reduction rate of lactate (ΔLact/h) was calculated individually from all lactate concentrations measured from inclusion until normalization of lactate (≤1.5 mmol/L) within 24 hours. The mortality at 30 days following ICU admission was evaluated. Results: Among 1405 ICU admissions during 2 years, 104 patients were eligible. Mortality rate at 30 days was 34%. The optimal cut‐off values of baseline lactate and ΔLact/h for 30‐day mortality were 4 mmol/L and 2.5%/h. When stratifying the patients by these cut‐points, those with baseline lactate > 4 mmol/L and ΔLact/h < 2.5%/h had lowest probability of survival (27%). Multivariable logistic regression showed that ΔLact/h <2.5%/h, baseline lactate >4 mmol/L and high Simplified Acute Physiology Score III were independent risk factors of 30‐day mortality. Conclusions: In this retrospective pilot cohort, a mean reduction rate of lactate <2.5%/h within the first 24 hours of ICU stay was associated with an increased risk of 30‐day mortality in septic shock patients.